Correlations between fractional flow reserve and a novel non-hyperemic index: resting full-cycle ratio in patients with an ambiguous coronary artery stenosis. (25th November 2020) - Szolc, P; Niewiara, L; Guzik, B; Horszczaruk, G; Podolec, J; Kleczynski, P; Zmudka, K; Buksinska-Lisik, M; Mamcarz, A; Legutko, J
Abstract: Background: Fractional flow reserve (FFR) measurement has been the gold standard for invasive assessment of coronary ischemia. Resting full cycle ratio (RFR) is a new non-hyperemic index used to define physiologic significance of coronary artery stenosis. However, there are limited data available to establish optimal cut-off value of RFR for decision making on revascularization. Aim: The aim of our study was to assess optimal cut-off value of RFR at which to predict FFR of 0.8. Methods: The RFR and FFR values were recorded during invasive coronary angiography in vessels with angiographic stenosis 40–70% according to visual assessment. Maximum hyperemia for FFR measurement was achieved with adenosine iv. infusion at 140 μg/kg/min. Left main disease, acute myocardial infarction and systolic left ventricular dysfunction (EF <40%) were the main exclusion criteria. Results: We evaluated 332 vessels, including 189 (56.9%) left anterior descending arteries, 77 (23.2%) left circumflex arteries and 66 (19.9%) right coronary arteries. Median diameter stenosis as assed by QCA was 45% (IQR 40; 50). Median RFR and FFR values were 0.90 [IQR 0.85; 0.94] and 0.86 [IQR 0.81; 0.92] respectively, with significant correlation (p<0.001, Figure 1, panel A). Optimal cut-off value for RFR to detect FFR 0.80 was 0.90 with area under the curve of 90.3%, sensitivity of 81.4% and specificity 88.0% (Figure 1, panel B). Conclusions: Our data confirm RFR cut-off value ≤0.90 as an optimal threshold to detect ischemic lesions with good sensitivity and specificity in comparison to FFR assessment. Further research is necessary to assess outcomes of RFR-guided revascularization strategy. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Jagiellonian University statutory grant